2016
DOI: 10.1016/j.clinph.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Spatial orientation in patients with chronic unilateral vestibular hypofunction is ipsilesionally distorted

Abstract: OBJECTIVE Acute unilateral peripheral-vestibular hypofunction (UVH) shifts the subjective visual vertical (SVV) ipsilesionally, triggering central compensation that usually eliminates shifts when upright. We hypothesized that compensation is worse when roll-tilted. METHODS We quantified SVV errors and variability in different roll-tilted positions (0°, ±45°, ±90°) in patients with chronic UVH affecting the superior branch (SVN; n=4) or the entire (CVN; n=9) vestibular nerve. RESULTS Errors in SVN and CVN were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 54 publications
(64 reference statements)
1
15
0
Order By: Relevance
“…Such distinct patterns of sensory contributions to perception of upright are supported by the findings in patients with vestibular and proprioceptive loss ( 25 , 78 87 ). Patients with vestibular loss tend to have no E-effect at small tilt angles and more pronounced A-effects at larger tilt angles, consistent with reduced weight of head position signals and consequently relative underestimation of upright orientation ( 25 , 80 82 , 84 , 86 , 87 ). Patients with proprioceptive loss, on the other hand, have decreased A-effect consistent with reduced weight of body proprioception, and consequently relative overestimation of upright orientation ( 25 , 88 , 89 ).…”
Section: Neurobehavioral Aspects Of Upright Perceptionmentioning
confidence: 66%
“…Such distinct patterns of sensory contributions to perception of upright are supported by the findings in patients with vestibular and proprioceptive loss ( 25 , 78 87 ). Patients with vestibular loss tend to have no E-effect at small tilt angles and more pronounced A-effects at larger tilt angles, consistent with reduced weight of head position signals and consequently relative underestimation of upright orientation ( 25 , 80 82 , 84 , 86 , 87 ). Patients with proprioceptive loss, on the other hand, have decreased A-effect consistent with reduced weight of body proprioception, and consequently relative overestimation of upright orientation ( 25 , 88 , 89 ).…”
Section: Neurobehavioral Aspects Of Upright Perceptionmentioning
confidence: 66%
“…The SVV primarily reflects asymmetry of utricular inputs between the sides of the vestibular system ( 12 ). The utricle responds to roll tilts and side-to-side translation of the head ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study described an enhanced A-effect during lateral body tilt in patients with bilaterally absent vestibular function and also ascribed it to somatosensory inputs ( 11 ). Meanwhile, patients with chronic unilateral peripheral vestibular hypofunction showed that adjustment errors of the SVV were pronounced during an ipsilesional tilt, more so in those with ipsilesionally absent ocular vestibular-evoked myogenic potentials (VEMPs) ( 12 ). These data support a dominant role of the utricle in perception of verticality during head tilts.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the effect of unilateral peripheral vestibular lesions on SVV was attributed to a tone imbalance of the otolith system (98). Use of a neural network model focusing on the direction of SVV tilts in the roll plane in upright and tilted body positions allowed comparison of the data from model simulations with clinical data (Figure 8).…”
Section: Methods Of Verticality Perceptionmentioning
confidence: 99%